Stillbirth is associated with increased risk of long-term maternal renal disease: a nationwide cohort study - Barrett, Peter M. (Am J Obstet Gynecol, 2020)
BACKGROUND: Stillbirth is a devastating adverse pregnancy outcome that may occur without any obvious reason or may occur in the context of fetal growth restriction, preeclampsia, or other obstetric complications. There is increasing evidence that women who experience stillbirths are at greater risk of long-term cardiovascular disease, but little is known about their risk of chronic kidney disease and end-stage renal disease. We conducted the largest study to date to investigate the subsequent risk of maternal chronic kidney disease and end-stage renal disease following stillbirth. OBJECTIVE: To identify whether pregnancy complicated by stillbirth is associated with subsequent risk of maternal chronic kidney disease and end-stage renal disease, independent of underlying medical or obstetric comorbidities. STUDY DESIGN/METHODS: We conducted a population-based cohort study using nationwide data from the Swedish Medical Birth Register, National Patient Register, and Swedish Renal Register. We included all women who had live births and stillbirths from 1973 to 2012, with follow-up to 2013. Women with preexisting renal disease were excluded. Cox proportional hazard regression models were used to estimate adjusted hazard ratios and 95% confidence intervals for associations between stillbirth and maternal chronic kidney disease and end-stage renal disease respectively. We controlled for maternal age, year of delivery, country of origin, parity, body mass index, smoking, gestational diabetes, preeclampsia, and small for gestational age deliveries. Women who had a history of medical comorbidities, which may predispose to renal disease (prepregnancy cardiovascular disease, hypertension, diabetes, lupus, systemic sclerosis, hemoglobinopathy, or coagulopathy), were excluded from the main analysis and examined separately. RESULTS: There were 1,941,057 unique women who had 3,755,444 singleton pregnancies, followed up over 42,313,758 person-years. The median follow-up time was 20.7 years (interquartile range, 9.9–30.0 years). 13,032 women (0.7%) had at least 1 stillbirth. Women who had experienced at least 1 stillbirth had a greater risk of developing chronic kidney disease (adjusted hazard ratio, 1.26; 95% confidence interval, 1.09–1.45) and end-stage renal disease (adjusted hazard ratio, 2.25; 95% confidence interval, 1.55–3.25) compared with women who only had live births. These associations persisted after removing all stillbirths that occurred in the context of preeclampsia, and small for gestational age or congenital malformations (for chronic kidney disease, adjusted hazard ratio, 1.33; 95% confidence interval, 1.13–1.57; for end-stage renal disease, adjusted hazard ratio, 2.95; 95% confidence interval, CI 1.86–4.68). There was no significant association observed between stillbirth and either chronic kidney disease or end-stage renal disease in women who had preexisting medical comorbidities (chronic kidney disease, adjusted hazard ratio, 1.13; 95% confidence interval, 0.73–1.75 or end-stage renal disease, adjusted hazard ratio, 1.49; 95% confidence interval, 0.78–2.85). CONCLUSION: Women who have a history of stillbirth may be at increased risk of chronic kidney disease and end-stage renal disease compared with women who have only had live births. This association persists independently of preeclampsia, and small for gestational age, maternal smoking, obesity, and medical comorbidities. Further research is required to determine whether affected women would benefit from closer surveillance and follow-up for future renal disease.